Analysis relationship of knowledge and bullying in adolescents - Arini, Ketut Novia; Wulandari, Ketut Ayu; Kusuma Dewi, Putu Dian Prima; Utari, Luh Vina (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2023)
Background: Bullying is an abuse of power or force that is carried out a person or group either physically or psychologically towards someone who unable to defend himself in a situation where there is a desire to injure, frighten or depress someone that has the potential to be repeated. Bullying can have a long-term impact on mental health and this will increase in adolescence with their low knowledge about aspects of bullying.Objectives: was To determine the relationship between knowledge and bullying behavior in adolescents at SMA Negeri 2 Gerokgak. Methods : This study used a quantitative research, with a cross sectional approach method . The population in this study were all students of class X. The sampling technique in this study was non-probability sampling using a purposive sampling technique.The total population in this study was 136 people and this study used of 101 respondents. The measuring instrument in this study is a questionnaire sheet about bullying. Data analysis using Pearson Product Moment. Results: Based on the results of the analysis, the p-value is 0.000 <0.05, which means that there is a significant relationship between the level of knowledge and bullying behavior with a correlation coefficient of -0.719 with a strong correlation strength and a negative correlation direction, which means that knowledge is in the opposite direction to behavior bullying which means the higher the knowledge, the lower the level of bullying behavior and vice versa.Conclusions: There is a correlation between the level of knowledge and bullying behavior at SMA Negeri 2 Gerokgak.